Las carreras políticas en Ecuador. El cambio de partido como estrategia para la obtención de votos - Zaruma Flores, Jorge Augusto (2017)
Political careers have generally been studied in three periods: beginning, development and end. A considerable number of phenomena have been identified during these three stages, and it is therefore important to analyze them for political science. Party change by politicians as a strategy to win votes is a phenomenon that has happened in Ecuador frequently; therefore, this study analyzes the reelection of Ecuadorian lawmakers from four provinces that have changed their political party, and compares their successes to those who were reelected in the same party. The reporting period, 2007 -2013, generated interesting results. The results indicate that the personal ambitions and selfinterests of these lawmakers were clearly present, and suggested that political ideology was futile in certain cases. The results also highlighted the importance of holding public office and of joining important parties prior to elections to ensure success. Moreover, the presence of successful political careers within party changes was more frequent in small provinces than in large provinces.